2009
DOI: 10.1016/j.mrfmmm.2009.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Defective interaction between Pol2p and Dpb2p, subunits of DNA polymerase epsilon, contributes to a mutator phenotype in Saccharomyces cerevisiae

Abstract: SummaryMost of the prokaryotic and eukaryotic replicative polymerases are multi-subunit complexes. There are several examples indicating that noncatalytic subunits of DNA polymerases may function as fidelity factors during replication process. In this work, we have further investigated the role of Dpb2p, a noncatalytic subunit of DNA polymerase epsilon holoenzyme from Saccharomyces cerevisiae in controlling the level of spontaneous mutagenesis. The data presented indicate that impaired interaction between cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…It has been established that the C-terminus of Dpb2p is important for its interaction with Pol2p [49]. Isolated in our laboratory dpb2 mutants exhibit temperature-sensitivity and mutator phenotype [47,48]. We observed a strong synergistic mutator effect between the mutant alleles of DPB2 and msh6 mutation suggesting that dpb2-dependent errors arising during DNA replication are substrates for mismatch repair system.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…It has been established that the C-terminus of Dpb2p is important for its interaction with Pol2p [49]. Isolated in our laboratory dpb2 mutants exhibit temperature-sensitivity and mutator phenotype [47,48]. We observed a strong synergistic mutator effect between the mutant alleles of DPB2 and msh6 mutation suggesting that dpb2-dependent errors arising during DNA replication are substrates for mismatch repair system.…”
Section: Introductionmentioning
confidence: 55%
“…We have previously isolated several temperature-sensitive mutant alleles of DPB2 encoding the non-catalytic subunit of Pol holoenzyme in the yeast S. cerevisiae [47,48]. The mutants were significantly affected in spontaneous mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature sensitive dpb2 alleles were shown to give an increased spontaneous mutation rate (Jaszczur et al 2008 ) . The level of spontaneous mutation rates were correlated with loss of interaction with Pol2 in two-hybrid assays (Jaszczur et al 2009 ) . Whether Dpb2 directly in fl uences the fi delity of Pol2 remains to be shown.…”
Section: Dpb2mentioning
confidence: 99%
“…These interact with a motif closer to the N-terminus of Pol2 (Shikata et al 2006 ) . Yeast two-hybrid assays have also shown that yeast Dpb2 interacts with the zinc-fi nger domain (Dua et al 1998 ;Jaszczur et al 2009 ) . It is entirely possible, therefore, that the very C-terminal domain of Pol2 extends away from the globular head domain and provides binding sites for the accessory subunits.…”
Section: Structure Of Pol E Holoenzymementioning
confidence: 99%